Little Minds, Growing Words: Language Acquisition in Early Toddlerhood - Pulungan, Novria; Marwah; Nasution, Fadhilah Syam; Khodijah, Siti; Ningsih, Devi Widya; Sitoru, Nadrah (Politeknik Negeri Sriwijaya, 2025)
Language acquisition during early childhood represents a critical stage in cognitive and social development. This study investigates the language acquisition of a two-year-old child living in Medan, Indonesia, focusing on vocabulary growth, sentence structure, and caregiver interaction. Using a qualitative descriptive approach, naturalistic observations were conducted over two weeks, documenting the child’s spontaneous speech and communicative exchanges. The findings reveal that the child produced approximately 75 distinct words, primarily nouns and verbs, reflecting daily routines and immediate surroundings. The child’s utterances were dominated by two-word combinations and telegraphic speech, consistent with Brown’s (1973) two-word stage. Caregiver interaction played a central role, with prompting, expansion, and feedback serving as scaffolding mechanisms that enriched the child’s linguistic development. Comparisons with recent studies confirm the universality of these developmental patterns while highlighting cultural and contextual influences on vocabulary and sentence use. This study contributes to the growing body of research on language acquisition in non-Western contexts and underscores the importance of caregiver support in fostering early language development. Keywords: language acquisition, two-year-old child, vocabulary development, telegraphic speech, caregiver interaction. DOI: https://doi.org/10.5281/zenodo.17528194